Analisis Implementasi Teknologi Building Information Modelling (BIM) pada Tahap Perencanaan Bangunan Gedung Istana Kepresidenan Ibu Kota Nusantara (Studi Kasus PT Yodya Karya, Persero) - Riyadi, Sugeng; Taqwa, Fadhila Muhammad Libasut; Brillianto, Ananta Giga; Simanjuntak, Manlian Ronald A. (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
As one of the applied technologies in infrastructure development, Building Information Modeling (BIM) facilitates the construction modeling process by providing information and tools that help the planning, construction and operation processes to be more efficient and effective. This research aims to evaluate the performance of BIM implementation in the project planning stage within PT Yodya Karya (Persero), with the object being the building planning stage for the Presidential Palace of the Indonesian Capital City of Nusantara (IKN), based on regulatory aspects of the procurement of goods and services. The method used in this research is a literature review in the form of Procurement TOR (Work Terms of Reference) data, Design and Built work contracts, as well as planning products such as Basic Design and Detailed Engineering Design (DED). Based on the research that has been carried out, the results can be obtained that there is an increase in digital work efficiency and productivity, to reduce various risks of errors and communications that occur in the field, by providing better design visibility and data management. In addition, the use of BIM at the planning stage can increase budget efficiency, project cycle duration, and work quality by paying attention to requirement stated on contract document.